Análisis del Cumplimiento de las Políticas de Venta de Almacenes PYCCA -K de la Ciudad de Babahoyo - Murillo Onofre, Jenny Bella (2018)
This case study allows us to analyze the compliance with the Sales Policies of PYCCA -K warehouses of the City of Babahoyo, this company has been considered by the fact of being an organization that is operating in different parts of the country, generating sources of work and reaching citizenship with quality products, manufactured by its industrial annex and also selling products for the home of recognized companies in Ecuador. This branch works in the city of Babahoyo since May 26, 2012.